Numerical investigation of 2-D free convection of nanofluid in L-shaped enclosure - Sidik, N. A. C. (2013)
This paper presents numerical investigations of the thermal and fluid flow behavior in an L-shaped of cavity filled with nanofluid. The left and bottom walls are heated to higher temperature than the horizontal upper and right vertical walls. The results show that the characteristic of flow and heat transfer are critically dependent on the dimensionless Rayleigh number. We also found that the presence of nanoparticle enhances the heat transfer rate in the enclosure.